Diversity of Emotional Intelligence among Nursing and Medical Students - Chun, Kyung Hee (Osong Public Health Res Perspect, 2016)
OBJECTIVES: The purpose of this study is to identify the types of perception of emotional intelligence among nursing and medical students and their characteristics using Q methodology, and to build the basic data for the development of a program for the would-be medical professionals to effectively adapt to various clinical settings in which their emotions are involved. METHODS: Data were collected from 35 nursing and medical students by allowing them to classify 40 Q statements related to emotional intelligence and processed using the PC QUANL program. RESULTS: The perceptions of emotional intelligence by nursing and medical students were categorized into three types: “sensitivity–control type”, “sympathy–motivation type”, and “concern–sympathy type”. CONCLUSION: The perceptions of emotional intelligence by nursing and medical students can represent an effective coping strategy in a situation where emotion is involved. In the medical profession, an occupation with a high level of emotional labor, it is important to identify the types of emotional intelligence for an effective coping strategy, which may have a positive effect on the performance of an organization. Based on the findings of this study, it is necessary to plan an education program for vocational adaptability for nursing and medical students by their types.